2023
DOI: 10.1371/journal.pone.0280271
|View full text |Cite
|
Sign up to set email alerts
|

Troll story: The dark tetrad and online trolling revisited with a glance at humor

Abstract: Internet trolling is considered a negative form of online interaction that can have detrimental effects on people’s well-being. This pre-registered, experimental study had three aims: first, to replicate the association between internet users’ online trolling behavior and the Dark Tetrad of personality (Machiavellianism, narcissism, psychopathy, and sadism) established in prior research; second, to investigate the effect of experiencing social exclusion on people’s motivation to engage in trolling behavior; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…They also coincide -albeit partially-with Buckels et al (2014), who found associations between Machiavellianism and psychopathy but did not detect correlations between narcissism and trolling. However, another study did find the latter association (Furian & March, 2023), while Craker and March (2016) and Volkmer et al (2023) detected significant correlations between psychopathy and R-GAIT. The fact that in the present study, trolling was associated both with Machiavellianism and psychopathy is not surprising due to the aggressive and manipulative features of trolling (Hardaker, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…They also coincide -albeit partially-with Buckels et al (2014), who found associations between Machiavellianism and psychopathy but did not detect correlations between narcissism and trolling. However, another study did find the latter association (Furian & March, 2023), while Craker and March (2016) and Volkmer et al (2023) detected significant correlations between psychopathy and R-GAIT. The fact that in the present study, trolling was associated both with Machiavellianism and psychopathy is not surprising due to the aggressive and manipulative features of trolling (Hardaker, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…Hypothesis 2 explored the relationships between dark humour and online trolling due to past research linking this behaviour to other negative styles of humour and katagelasticism [ 10 , 42 ]. Hypothesis 3, overall, aimed to better understand online trolls.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative research has sought to explain individual differences in trolling behaviours through personality approaches and humour-related motivations. Several studies [ 9 , 40 , 41 , 42 ] found psychopathy, as well as Machiavellianism and sadism, most strongly predicted online trolling. For instance, [ 9 ] concluded that online trolling is an “internet manifestation of everyday sadism” and that the internet is essentially a sadist “playground”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motives for engaging in online anti-social behavior are varied, as studies have indicated. Social media users may participate in such acts for various reasons, including seeking revenge, seeking amusement, seeking social approval, displaying sadistic tendencies, or simply due to a lack of empathy (e.g., Santre, 2023; Soares et al, 2023; Vismara et al, 2022; Volkmer et al, 2023).…”
Section: Introductionmentioning
confidence: 99%